Robert Godlonton as architect of frontier opinion, with special reference to the politics of separatism, 1850-57 - Le Cordeur, Basil Alexander (Rhodes University, Faculty of Humanities, Department of History, 1956)
[Preface] The broad outlines of Cape frontier historiography have so far been sketched from a study of official despatches and, to a lesser extent, of contemporary newspapers. There are many lacunae to be filled and many questions to be answered; here, it is evident that private papers have an indispensable role to play. Yet, despite isolated attempts to collect or index such papers, (such as that of Miss Una Long, in her Index to Unofficial, Privately-Owned Manuscripts relating to the history of South Africa), much untapped material still remains in private possession both in South Africa and overseas. In this study of a leading Eastern Province personality, prominence has been given to this type of material, and much of what has been used, has clearly not previoualy been examined by historians.
Keywords: Godlonton, Robert, 1794-1884; Cape of Good Hope (South Africa) -- History -- 1795-1872; Cape of Good Hope (South Africa) -- Politics and government -- 1795-1872; Press and politics -- South Africa -- Cape of Good Hope; Editors -- South Africa -- History